Progress Toward a Gonococcal Vaccine: The Way Forward - Russell, Michael W.; Jerse, Ann E.; Gray-Owen, Scott D. (Frontiers in Immunology, 2019)
The concept of immunizing against gonorrhea has received renewed interest because of the recent emergence of strains of Neisseria gonorrhoeae that are resistant to most currently available antibiotics, an occurrence that threatens to render gonorrhea untreatable. However, despite efforts over many decades, no vaccine has yet been successfully developed for human use, leading to pessimism over whether this goal was actually attainable. Several factors have contributed to this situation, including extensive variation of the expression and specificity of many of the gonococcal surface antigens, and the ability of N. gonorrhoeae to resist destruction by complement and other innate immune defense mechanisms. The natural host restriction of N. gonorrhoeae for humans, coupled with the absence of any definable state of immunity arising from an episode of gonorrhea, have also complicated efforts to study gonococcal pathogenesis and the host’s immune responses. However, recent findings have elucidated how the gonococcus exploits and manipulates the host’s immune system for its own benefit, utilizing human-specific receptors for attachment to and invasion of tissues, and subverting adaptive immune responses that might otherwise be capable of eliminating it. While no single experimental model is capable of providing all the answers, experiments utilizing human cells and tissues in vitro, various in vivo animal models, including genetically modified strains of mice, and both experimental and observational human clinical studies, have combined to yield important new insight into the immuno-pathogenesis of gonococcal infection. In turn, these have now led to novel approaches for the development of a gonococcal vaccine. Ongoing investigations utilizing all available tools are now poised to make the development of an effective human vaccine against gonorrhea an achievable goal within a foreseeable time-frame.